COMPREHENSIVE ASSESSMENT OF THE QUALITY OF GAS FROM RECOVERED FIBERS (Multidisciplinary Journal of Science and Technology, 2025)
in this article, the complex evaluates the physical and mechanical properties of fabrics obtained from a mixture of different compositions and recycled fibers at the joint venture of Safira-Samira Textile LLC, EURASIYA ALLIANCE TEX LLC in the Bukhara region and CHACH TEX LLC in the Chirchik district of Tashkent area and recommended the best option.